Anthelmintic Activity of Crude Extract and Essential Oil of Tanacetum vulgare (Asteraceae) against Adult Worms of Schistosoma mansoni - Loyana Silva Godinho; Lara Soares Aleixo de Carvalho; Clarissa Campos Barbosa de Castro; Mirna Meana Dias; Priscila de Faria Pinto; Antônio Eduardo Miller Crotti; Pedro Luiz Silva Pinto; Josué de Moraes; Ademar A. Da Silva Filho (The Scientific World Journal)
Schistosomiasis, a parasitic disease caused by trematode flatworms of the genus Schistosoma, affects more than 200 million people worldwide, and its control is dependent on a single drug, praziquantel. Tanacetum vulgare (Asteraceae) is used in folk medicine as a vermifuge. This study aimed to investigate the in vitro schistosomicidal activity of the crude extract (TV) and the essential oil (TV-EO) from the aerial parts of T. vulgare. TV-EO was obtained by hydrodistillation and analyzed by GC/MS, which allowed the identification of β-thujone (84.13%) as the major constituent. TV and TV-EO, at 200 μg/mL, decreased motor activity and caused 100% mortality of all adult worms. At 100 and 50 μg/mL, only TV caused death of all adult worms, while TV-EO was inactive. TV (200 μg/mL) was also able to reduce viability and decrease production of developed eggs. Confocal laser scanning microscopy showed morphological alterations in the tegument of the S. mansoni surface after incubation with TV (50 and 100 μg/mL). Quantitative analysis on the schistosomes tegument showed that TV caused changes in the numbers of tubercles of S. mansoni male worms in a dose-dependent manner. The findings suggest that T. vulgare is a potential source of schistosomicidal compounds.